2021
DOI: 10.3390/fluids6080272
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Delivery in Prostate Tumors Implanted in Mice Facilitated by Either Local or Whole-Body Heating

Abstract: This work discusses in vivo experiments that were performed to evaluate whether local or whole-body heating to 40 °C reduced interstitial fluid pressures (IFPs) and enhanced nanoparticle delivery to subcutaneous PC3 human prostate cancer xenograft tumors in mice. After heating, 0.2 mL of a previously developed nanofluid containing gold nanoparticles (10 mg Au/mL) was injected via the tail vein. The induced whole-body hyperthermia led to increases in tumor and mouse body blood perfusion rates of more than 50% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Elevated IFP would prevent anticancer agents from entering deeper tumor tissue (Kozono et al, 2013; Nikmaneshi et al, 2021). Gu et al have shown that whole‐body hyperthermia can lead to significant reductions in the IFPs of PC3 tumors and an increase in the blood perfusion rates in the mouse body after heating (Gu et al, 2021). In addition, according to Gu et al's research in 2020, significant IFP decreases of 45% immediately after heating, 47% 2 h later, and 52% 24 h later were seen in the experimental group (Gu et al, 2020).…”
Section: Effects Of Hyperthermia On Drugs Uptake and Targetingmentioning
confidence: 99%
“…Elevated IFP would prevent anticancer agents from entering deeper tumor tissue (Kozono et al, 2013; Nikmaneshi et al, 2021). Gu et al have shown that whole‐body hyperthermia can lead to significant reductions in the IFPs of PC3 tumors and an increase in the blood perfusion rates in the mouse body after heating (Gu et al, 2021). In addition, according to Gu et al's research in 2020, significant IFP decreases of 45% immediately after heating, 47% 2 h later, and 52% 24 h later were seen in the experimental group (Gu et al, 2020).…”
Section: Effects Of Hyperthermia On Drugs Uptake and Targetingmentioning
confidence: 99%